(untitled) (Colombia Medica, 2012)
Objective: To evaluate the hematological, cytogenetic, and molecular responses in Colombian patients with CML chronic myeloid leukemia (CML) treated with imatinib. Methods: Two groups of patients, one with the novo diagnostic and another in state of complete cytogenetic remission were followed for 12 months with quantitative PCR evaluations every three months and with chromosomal analysis every 6 months. Results: The group with the novo diagnosis showed 50% of complete cytogenetic remission at 12 months while the other 50% were considered to have primary resistance. Respect the molecular analysis, 10.5% of the patients reached undetectable BCR-ABL transcripts at 12 months. In the complete cytogenetic remission group, 10.6% lost the state of complete cytogenetic remission at 12 months, 50% reached undetectable BCR-ABL transcripts but 10% showed levels higher than 10%, which in our standardization was equal to no molecular response. Conclusions: Despite having received the conventional dosages of 400 mg/day of imatinib, the cytogenetic and molecular responses obtained in our group of Colombian patients with CML, were lower than those in other international studies.